Physiological and psychological performance of taekwondo athletes is more affected by rapid than by gradual weight reduction - Yang, W.-H.; Grau, M.; Kim, P.; Schmitz, A.; Heine, O.; Bloch, W.; Mester, J. (Archives of Budo, 2014)
Background and Study Aim: The results of previous studies regarding the impact of different forms of weight reduction on performance capacity are not consistent. Therefore, the purpose of this study was the knowledge about the effects of RWR and GWR in Taekwondo athletes on physiological and psychological changes and performance with the sport specific investigation. Materials and Methods: After baseline measurements, participants reduced weight by 5% within four days (RWR) followed by subsequent measurements. Additional measurements were performed one day post RWR followed by another two baseline measurements in the following weeks before the participants had to reduce 5% of their weight within four weeks (GWR). A final measurement was conducted one day post GWR. Anthropometry, vertical jumps, kick-frequencies and lactate production rate were assessed. Blood glucose, creatine kinase, creatinine, urea and electrolytes were analysed reflecting physiological changes after weight reduction. The psychological analyses comprised an adjective list of Perceived Physical State (PEPS). Results: Body weight and water were significantly decreased after RWR and GWR (p<0.01) but body fat was only significantly decreased after GWR (p<0.01). Vertical jumps were significantly higher after RWR and kick-frequencies were higher after GWR (p<0.01). The impairments of blood indicators and scale values of PEPS were more predominant in RWR (p<0.05, p<0.01). Conclusions: Overall, better results regarding physiological and psychological performances were achieved after GWR. Trainers and athletes should schedule GWR to achieve the desired weight prior to a competition so that a potential decline in performance can be avoided.